2003
DOI: 10.1164/rccm.200209-1030oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Structural Alterations Selectively Associated with Severe Asthma

Abstract: To identify airway pathologic abnormalities selectively associated with severe asthma, we examined 10 control subjects, 10 patients with intermittent asthma, 15 patients with mild-to-moderate persistent asthma, 15 patients with severe persistent asthma, and 10 patients with chronic obstructive pulmonary disease. Bronchial biopsies were assessed for epithelial integrity; subepithelial basement membrane (SBM) thickness; collagen type III deposition; eosinophil, neutrophil, and fibroblast numbers; mucous gland an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
641
4
24

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 720 publications
(704 citation statements)
references
References 59 publications
35
641
4
24
Order By: Relevance
“…Vessels within the submucosa plexus have since 13 then been reported extensively to be increased in the asthmatic airway. The subepithelial space is shortened in asthmatics and this correlates to disease severity [76], bringing the increased ASM bundles into close proximity to the submucosa plexus. Thickening of the airway wall in asthma also includes increased vessel calibre as a result of dilatation of capillary vessels, angiogenesis, oedema from microvascular leakage, increased capillary permeability and engorgement of lymphatic and blood capillaries.…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 99%
“…Vessels within the submucosa plexus have since 13 then been reported extensively to be increased in the asthmatic airway. The subepithelial space is shortened in asthmatics and this correlates to disease severity [76], bringing the increased ASM bundles into close proximity to the submucosa plexus. Thickening of the airway wall in asthma also includes increased vessel calibre as a result of dilatation of capillary vessels, angiogenesis, oedema from microvascular leakage, increased capillary permeability and engorgement of lymphatic and blood capillaries.…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 99%
“…Many of these patients are labelled as corticosteroid-dependent, in that reduction in either maintenance ICS or oral CS leads to a deterioration of asthma control. Studies have reported that there is persistent neutrophilic and eosinophilic inflammation [78,79] in the airways, together with increased subbasement membrane thickness and airway smooth-muscle mass [80,81]. There is altered expression of markers of epithelial proliferation such as an increased expression of the proliferation marker, Ki67, and reduced expression of Bcl-2, a negative regulator of epithelial cell death [82].…”
Section: Corticosteroid Insensitivity In Airways Diseasementioning
confidence: 99%
“…The airways of patients with asthma typically display a number of structural changes, including goblet cell metaplasia and excessive mucus production, thickening of the lamina reticularis, angiogenesis, and increased smooth muscle mass with a reduced distance between muscle cells and the airway epithelium as asthma severity increases (1,2). These changes, collectively termed airway remodeling, lead to a thickening of the airway wall.…”
Section: Introductionmentioning
confidence: 99%